PENILAIAN KERUGIAN ABNORMAL PADA BUDIDAYA UDANG Studi Kasus Budidaya Udang di MSTP (Marine Science Techno Park) Universitas Diponegoro Jepara, Jawa Tengah - Fitri Alfiyana; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2025)
This study aims to detected and assess abnormal losses in shrimp farming, especially whiteleg shrimp. Managing abnormal losses is very important in business so that losses do not get bigger. One of the main reasons is to maintain the company’s profit margin. Abnormal losses can increase cost and reduce income, which can ultimately reduce profit margins. This study was conducted using a descriptive-quantitave methode on a case study of whiteleg shrimp farming at MTSP (Mariene Science Techno Park) Diponegoro University, Jepara, Central Java, which consists of two clussters with seven cycles in each cluster. The data used include production costs. The calculations used are based on cost accounting principles.The results of the study showed that shrimp farming identified abnormal losses in three cost components, namely electricity cost-cycle 1, fuel cost-cycle 6, mechanical cost-cycle 1 (Cluster A) and electricity cost-cycle 5, fuel costs-cycle 6, mechanical cost-cycle 2 (Cluster B). Abnormal loss assessment is done by comparing actual costs with the average normal costs. The difference in costs is considered an abnormal loss if it does not have a positive impact on increasing crop yield. It is known that the abnormal loss value in Cluster A is IDR 45.710.159 and in Cluster B is IDR 41.827.364. Implementation of a cost control system that is integrated with the production cycle is very necessary to enable a periodic and real-time evaluation process of the most crucial cost components.